Transformasi Pembelajaran Pancasila Berbasis Literasi Visual melalui Media Canva pada Siswa Sekolah Dasar - Nurkholifah, Anisa; Nisa, Khoirun; Juwita , Ratan (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study examines the use of Canva to improve elementary school students' visual skills and understanding of Pancasila values in Civics (PPKn) learning. Several obstacles, such as limited internet access and teachers' lack of skills, encourage innovation through interactive visual learning using Canva. This media provides features such as posters, videos, and animations that make learning materials more engaging and easier for students to understand. This study used a literature review method by analyzing 17 articles from Google Scholar using the keyword